Leveraging microenterprise products at the global market : a strategy to ensure sustainable poverty alleviation - Saidu, Mohammed Bashir; Abu Samah, Asnarulkhadi; Redzuan, Ma`arof; Ahmad, Nobaya (Center for Promoting Ideas (CPI), USA, 2013)
Across developing countries, microfinance has emerged as an effective tool for poverty reduction. It enables microenterprenuers to get access to finance, income generation, build assets, as well ascreating opportunities for poor households to plan for future. This article discusses the role of microfinance as a tool for poverty alleviation and potential of microenterprise products to global market. Previous literature revealed that microfinance institutions have contributed tremendously in poverty reduction through creation of microenterprises, or otherwise strengthened the existing microenterprises in developing nations. Based on the reviewed literature, the authors argued that the scope of microenterprise is beyond poverty alleviation but rather, its contribution to both domestic and international market. The authors recommend that government in developing countries apart from policy formulation and regulations on microfinance institutions however, should also be responsible for creating market for microenterprises products at both domestic and international levels.